Generation of high order multi-bound solitons and propagation in optical ﬁbers - Nguyen, Duc Nhan (Elsevier, 2013)
We demonstrate experimental generation of multi-bound solitons of up to sextuple in an active FM Received 16 October 2008 mode-locked ﬁber ring laser operating under power saturation in the locking state. The ring laser consists Received in revised form 27 February 2009 of two booster optical ampliﬁers operating in saturation regime, an electro-optic phase modulator driven Accepted 27 February 2009 by a sinusoidal electrical wave and a length of dispersive ﬁber. The periodic phase modulation generates phase chirp of the generated lightwaves in the ring laser. The chirped phase state plays an important role in the phase matching condition for mode-locking as well as the stabilization and the determination of Keywords: the bound states of multi-solitons. The formation of such high order multi-bound solitons is explained Fiber lasers Solitons based on the chirping of the phase and the behavior of the optical pulse sequence in the near ﬁeld region Phase modulation of the dispersive ﬁber. The propagation of these multi-bound solitons through single mode optical ﬁbers is observed. Experimental and simulation results of bound solitons have been shown to follow similar trends. The propagation of these multi-bound solitons through single mode optical ﬁbers is described. Their mutual interaction through such quadratic phase media shows the inﬂuence of the quadratic phase prop- erty on the differential phase of individual solitons of the bound group. Simulated results conﬁrm the evolution of the bound solitons over dispersive single mode optical ﬁbers.